Tunneling Nanotube-like Structures in Giardia duodenalis - Midlej, Victor (2024)
Giardia doudenalis (lamblia, intestinalis) is a protozoan parasite that inhabits the lumen of the upper small intestine of vertebrates, causing chronic abdominal pains and severe diarrhea, symptoms of giardiasis, a persistent and recurrent infection. This characteristic is mainly due to the presence of membrane variant-specific surface proteins (VSPs) that give this parasite the ability to successively infect the host through antigenic variation. Using high-resolution scanning microscopy (HR-SM), we observed the presence, formation, and extension of tunneling-nanotube-like surface structures in Giardia, especially following parasite challenges with VSP antibodies. They were seen all over the parasite surface, both in vitro and in vivo, showing that G. duodenalis nanotube formation occurs in complex environments such as the gut. In addition, we also observed that some of these nanotubes displayed a periodic strangulation that produces 100 nm vesicles that seemed to be released in a process similar to that previously observed in Trypanosoma brucei. The presence of nanotube-like structures in G. duodenalis highlights yet another strategy of cellular communication utilized by these parasites, whether between themselves or with the host cell.